Семантическая неопределенность цветообозначений в польском и русском языках (на материале лексикографических данных) - Andrzej Narloch (Studia Rossica Posnaniensia)
Color lexis constitutes a complex semantic network of meanings, which sometimes makes it difficult to determine the characteristic feature of a given color name. This article analyzes the semantic ambiguity of color lexis in the Polish and Russian languages. Color ambiguity, as shown by the analysis, is related to the specificity of the color pattern, the lack of stability of the color pattern or its multicolour quality.